Pengaruh Tunjangan Kinerja dan Disiplin Kerja Terhadap Kinerja Pegawai Sekretariat Inspektorat Jenderal Kementerian Pertanian - Basuki Basuki; A.H. Rahadian (Jurnal Ilmu Administrasi Publik, 2021)
This study aims to analyze the influence of Performance Allowances and Work Discipline toward Employees Performance both partially and simultaneously. The research uses a quantitative approach. The sample in this study amounted to 73 people using the Slovin formula to determine the number of samples. The research instrument used a questionnaire and variable measurement using a Likert scale with the characteristics of respondents were Civil Servants at the Secretariat of the Inspectorate General of the Ministry of Agriculture. Performance allowances (X1) and work discipline (X2) as independent variables will be tested simultaneously (simultaneously) their effect on the performance of civil servants (Y) as the dependent variable. Test the direct effect (partial) of performance benefits (X1) on the performance of civil servants (Y) and examine the direct (partial) effect of work discipline (X2) on the performance of civil servants (Y). The data was analyzed quantitatively using analytical tools in the form of validity test and reliability tested with IBM SPSS version 23 program. The results of the study state that performance allowances (X1) and work discipline (X2) have a positive and significant effect on the performance of civil servants (Y). Performance allowance (X1) has no significant effect on the performance of civil servants (Y) and work discipline (X2) has a positive and significant effect on the performance of civil servants (Y).